Changes of NK cell subsets with time post-transplant in peripheral blood of renal transplant recipients - Zhu, Li; Aly, Mostafa Gaafa; Morath, Christian; Kuon, Ruben-Jeremias; Ekpoom, Naruemol; Opelz, Gerhard; Daniel, Volker (Transplant immunology, 2018)
Background - There is evidence that NK cells with low cytotoxicity but strong immunoregulatory characteristics contribute to good graft outcome. We attempted to investigate which NK cell subsets increase post-transplant and might affect graft function. - Method - Lymphocyte and NK cell subsets were determined in whole blood using eight-colour-fluorescence flow cytometry in patients pre-transplant and post-transplant. In total, 31 transplant recipients were studied. - Results - When cell numbers were compared in 9 patients pre- and 6months post-transplant, post-transplant CD56dimCD16+ (p=0.011) NK cells with the phenotype CD158a+ (p=0.008), CD158e+ (p=0.038), NKG2A+ (p=0.008), NKG2D+ (p=0.011), IFNyR+ (p=0.008), perforin+ (p=0.008), granzymeB+ (p=0.008), perforin+granzymeB+ (p=0.008) and perforin-granzymeB- (p=0.021) were lower than those pre-transplant, indicating a post-transplant reduction of cytotoxic NK cells. In 28 patients NK cell subsets were analyzed with respect to time post-transplant (median 888days post-transplant). CD56dimCD16+ NK cells co-expressing CD158a (p=0.014), NKG2D (p=0.047), IL4R (p=0.038), IL10R (p=0.008) and IFNy (p=0.036) as well as CD56bright NK cells with the phenotype TGFß+ (p=0.017), TGFR+ (p=0.035), CD158a+ (p=0.042) and perforin-granzymeB- (p=0.048) increased with time post-transplant. - Conclusion - Post-transplant, cytotoxic NK cells were lower than pre-transplant and remained low, whereas NK cell subsets with potentially immunoregulatory properties increased.